2016
DOI: 10.1002/fam.2365
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and mechanical transient behaviour of steel doors installed in non‐load‐bearing partition wall assemblies during exposure to the standard fire test

Abstract: SUMMARY In this paper, the authors present experimental results and observations of four full‐scale standard fire tests on single‐leaf steel doors and steel frames installed in 3 × 3 m non‐load‐bearing partition walls. Three full‐scale fire tests were performed on steel doors installed in lightweight partition walls constructed by using steel C‐section studs with gypsum boards fixed on both sides. Two lightweight walls incorporated Rockwool cavity insulation, while the third lightweight wall was constructed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Considering the wall deformation with external load (load-bearing) already showed that the position of the maximum deformation was shifting. 7 The mechanical load on a wall from an expanding test specimen during FRTs was not reported in literature so far, besides recent studies of Prieler et al 25 and Nassif et al 26…”
Section: Literature Review-deformation Of the Walls During Frtsmentioning
confidence: 96%
See 1 more Smart Citation
“…Considering the wall deformation with external load (load-bearing) already showed that the position of the maximum deformation was shifting. 7 The mechanical load on a wall from an expanding test specimen during FRTs was not reported in literature so far, besides recent studies of Prieler et al 25 and Nassif et al 26…”
Section: Literature Review-deformation Of the Walls During Frtsmentioning
confidence: 96%
“…Considering the wall deformation with external load (load‐bearing) already showed that the position of the maximum deformation was shifting 7 . The mechanical load on a wall from an expanding test specimen during FRTs was not reported in literature so far, besides recent studies of Prieler et al 25 and Nassif et al 26 Prieler et al measured the wall deformation during FRTs when a single leaf door was tested. It was determined that the presence of the door was shifting the position of the maximum deformation of the brick wall significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The relevant test results were used to assess differences in the fire behavior of hinged doors under natural fire scenarios compared to stan- dard fire testing. Nassif et al [8] conducted standard fire tests on single-leaf steel doors which were mounted on drywall or masonry walls. In this study, the direction of door opening as well as the type of wall frame were found to significantly affect the fire resistance rating.…”
Section: State Of the Artmentioning
confidence: 99%
“…The proposed numerical model is compared with the corresponding experimental results in terms of temperature and deflection measurements, while sensitivity analyses are carried out to investigate the effect of the main modeling parameters. Relevant numerical studies are very limited in the literature due to the scarcity of experimental fire test results (Tabaddor and Jadhav, 2013;Joyeux, 2002;Nassif et al, 2016;Tabaddor et al, 2009;Capote et al, 2013;Boscariol et al, 2015). The numerical methodology and recommended practices for modeling the thermo-mechanical behavior of steel structures are discussed in support of the performance-based fire design standards.…”
Section: Fire Behavior Of Steel Structuresmentioning
confidence: 99%
“…The proposed numerical model is compared with the corresponding experimental results in terms of temperature and deflection measurements, while sensitivity analyses are carried out to investigate the effect of the main modeling parameters. Relevant numerical studies are very limited in the literature due to the scarcity of experimental fire test results (Tabaddor and Jadhav, 2013; Joyeux, 2002; Nassif et al. , 2016; Tabaddor et al.…”
Section: Introductionmentioning
confidence: 99%